Dual Function of Par3 in Tumorigenesis - Lv, Tao; Xu, Jiashun; Yuan, Hemei; Wang, Jianling; Jiang, Xinni (Frontiers in Oncology, 2022)
Cells maintenance and establishment of cell polarity involve complicated interactions among multiple protein complexes as well as regulation of different signaling pathways. As an important cell polarity protein, Par3 is evolutionarily conserved and involved in tight junction formation as well as tumorigenesis. In this review, we aimed to explore the function of Par3 in tumorigenesis. Researchers have shown that Par3 exhibits dual functions in human cancers, both tumor-promoting and tumor-suppressive. Here, we focus on the activities of Par3 in different stages and types of tumors, aiming to offer a new perspective on molecular mechanisms that regulate the function of Par3 in tumor development. Tumor origin, microenvironment, tumor type, cell density, cell-cell contact, and the synergistic effect of Par3 and other tumor-associated signaling pathways may be important reasons for the dual function of Par3. The important role of Par3 in mammalian tumorigenesis and potential signaling pathways is context-dependent.